Floating Home - Avdeev, Michael (Advances in Social Sciences Research Journal, 2026)
Floating homes are any structures that can float or submerge and travel on substantial distances while being completely sustainable and allowing its inhabitants to remain at sea for a prolonged period. Floating homes are sustainable alternative to traditional land-based housing for a variety of reasons. This paper sets out to establish that floating homes are more sustainable than traditional land-based homes due to their adaptability to rising sea levels, reduced land consumption, enhanced energy efficiency through passive cooling systems and innovative waste management practices.